94.0k views
4 votes
Find the mistake. How would you solve this problem correctly? plz answer btw those a minus this is due at 11: 59

6(x+4)=3x-2
6x+4=3x-2
3x+4= -2
3x+4-4= -2 -4
3x= -6
x= -2

User Rommudoh
by
4.6k points

1 Answer

5 votes

Answer:

The mistake is in the second "problem" or the second part

Explanation:

solve correctly by using pemdas when there are parenthesis but only "one" number (4) and a variable (x) you multiple (bring over the 6 and times both) leaving you with 6x + 24

User Axel Andersen
by
5.2k points